(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Uzbek language has three dialects: Qarluq (Tashkent, Andijan, Fergana, Samarkand, Bukhara, Karshi) Kipchak (Samarkand, Jizzakh, Surkhandarya, Karakalpakstan, North Khorezm regions, dialects of Tashkent region of Turkmenistan) Oguz dialect (Urgench, Khiva, Xonqa, Hazarasp, Koshkopir, Shavat districts). These dialects have their own characteristics and history of formation. Uzbek differs from other Turkic languages by the large number of dialects.